The Gap in Knowledge about Tapering Targeted Therapy being used as Monotherapy in Rheumatoid Arthritis: A Systematic Review - Thadepalli, Srivani; Amsamani, Sundarvel; Meng, Charis F.; Rajesh, Diviya A.; Jannat-Khat, Deanna P.; Jivanelli, Bridget; Bykerk, Vivian (Current Rheumatology Reviews, 2024)
Background: Up to 30% of patients with RA are being treated with biologic (b)-disease modifying anti-rheumatic drugs (DMARDs) as monotherapy. Monotherapy with Interleukin (IL)-6 inhibitors(i) and Janus-kinase (JAK)-i has been shown to be effective. Whether patients can taper targeted therapy (bDMARDs and JAK-i) used as monotherapy (targeted monotherapy) is unknown.Objective: To determine the feasibility of tapering of targeted monotherapy in patients with controlled RA.Methods: We conducted a literature search in Medline, Embase and Cochrane Library for prospective studies reporting remission outcomes after tapering targeted monotherapy in RA patients, from 1/2014 - 8 /2021.Results: 5 randomized studies which met our inclusion criteria, evaluating tapering of monotherapy with tumor necrosis factor-inhibitors, tocilizumab, abatacept and baricitinib in RA. Studies were heterogeneous. Three trials studied early RA. Three studies gradually tapered therapy, including 1 dose reduction study. Three studies tapered both biological and conventional-synthetic (cs)-DMARDs. No study compared stopping targeted monotherapy to continuing it. Remission rates were low 14-28% across all studies that stopped targeted monotherapy. The highest remission rate of 72% was reported by the dose reduction study. Trials that studied early RA reported remission rates after tapering ranging 27-72%. Trials tapering therapy in established RA reported rates of remission from 14-20%.Conclusion: There is a crucial gap in published literature to inform on tapering targeted monotherapy in patients with RA. Stopping targeted monotherapy is unlikely to maintain disease control in RA. Dose reduction strategies and early treatment of disease may be associated with more successful tapering, and warrant future study.
Keywords: natural reducing agents